Shipping Governance in the Polar Regions: the Interaction of Global, Regional and National Regimes - Donehue, Kaye Julia (UiT Norges arktiske universitet, 2018)
The primary question of the thesis is: What are the constraints and opportunities of shipping regulation at the regional and national level in the polar regions in light of overarching regulatory regimes? The framework instrument of maritime law is the 1982 United Nations Convention on the Law of the Sea (LOSC). Global shipping governance is regulated by the polar shipping standards of the IMO, including the Polar Code. International shipping law interacts with the unique regional and national regulations of the Arctic and Antarctic.